SUPERVISI KLINIS SEBAGAI UPAYA PENINGKATAN KOMPETENSI PEDAGOGIK GURU DALAM KEGIATAN BELAJAR MENGAJAR ERA PANDEMIK DI SDN KALIBANTENG KULON 01 SEMARANG - Wahyuningsih, Wiji Sri (Persatuan Guru Republik Indonesia Kota Semarang, 2021)
Teachers of SDN Kalibanteng Kulon 01 Semarang city, at the beginning of the Covid-19 pandemic pedagogic competence in teaching and learning activities, teachers lacked technology mastery, the power of smartphones did not support downloading online learning support applications, quotas were wasteful, and signal was difficult, another thing is when teachers must create materials and assignments that are easily translated by parents and students. Online learning has many obstacles, especially communication, because the teaching pattern is only through short Whatsapp group messages or Google Classroom. In order to be successful in carrying out their duties, of course, teachers must have a set of abilities in the field to be delivered as well as the ability to convey material (material) so that it is easily accepted by their students, therefore teachers need to get clinical supervision from the principal so that there is an increase in pedagogic competence in teaching and learning activities. pandemic era. This study is intended to answer the problem of whether the implementation of clinical supervision can improve pedagogic competence in teaching and learning activities in the pandemic era at SDN Kalibanteng Kulon 01, Semarang city in 2020/2021?. These problems are discussed through school action research which is carried out through 2 cycles with each cycle the stages are planning, action, observation and reflection. The results show that the implementation of clinical supervision can improve pedagogic competence in teaching and learning activities in the pandemic era at SDN Kalibanteng Kulon 01 Semarang city in 2020/2021, this can be seen from the increase in the results of teacher professionalism in classroom administration management per cycle where in the first cycle there are 5 teachers. or 62.5% and in the second cycle there were 7 teachers or 87.5%. These results indicate that these results are in line with expectations. The increase is the implementation of mini workshops to be one effective way for school principals in improving the ability of teachers in preparing learning tools